DINAMIKA HUKUM DAN SOSIAL KASUS PERCERAIAN AKIBAT “KDRT” DI PENGADILAN AGAMA ARSO KABUPATEN KEEROM PROVINSI PAPUA - Musrifah; Faisal; Moh Wahib (Istiqra: jurnal hasil penelitian, 2025)
This study aims to analyze the legal factors that influence the decision of victims of domestic violence (DV) to choose divorce rather than criminal law. In addition, this study evaluates the implementation of Law Number 23 of 2004 concerning the Elimination of Domestic Violence (UU PKDRT) in providing protection to victims. The method used in this study is field research with a normative legal and normative theological approach. Data collection techniques are carried out through in-depth interviews, observation, and document analysis, while data analysis techniques use qualitative descriptive methods to understand how the law is implemented in cases of divorce due to DV. The results of the study indicate that victims of DV prefer divorce because of the long criminal law process, minimal legal support for victims, and social pressure that considers DV as a family matter. The main obstacles in accessing justice include bias from law enforcement officers, limited evidence of non-physical violence, and lack of protection facilities such as safe houses. The novelty of this study lies in the analysis of the role of judges in deciding cases of DV divorce and identifying the need for legal reform to be more in favor of victims. Recommendations for future research include increasing the capacity of legal officers, educating the public about victims' rights, and integrating legal and psychosocial services to support victims in obtaining justice.